The presence of Camoes : influences on the literature of England, America, and Southern Africa - Monteiro, George (Studies in Romance languages (Lexington, Ky.), 1996)
Of the great epic poets in the Western tradition, Luis Vaz de Camões (c. 1524- 1580) remains perhaps the least known outside his native Portugal, and his influence on literature in English has not been fully recognized. In this major work of comparative scholarship, George Monteiro thus breaks new ground, focusing on English-language writers whose vision and expression have been sharpened by their varied responses to Camões. Introduced to English readers in 1655, Camões's work from the beginning appealed strongly to writers. The young Elizabeth Barrett's Camonean poems, for example, inspired ...